2019
DOI: 10.1097/ta.0000000000002483
|View full text |Cite
|
Sign up to set email alerts
|

Use of ShotSpotter detection technology decreases prehospital time for patients sustaining gunshot wounds

Abstract: BACKGROUND Shorter prehospital time in patients sustaining penetrating trauma has been shown to be associated with improved survival. Literature has also demonstrated that police transport (vs. Emergency Medical Services [EMS]) shortens transport times to a trauma center. The purpose of this study was to determine if ShotSpotter, which triangulates the location of gunshots and alerts police, expedited dispatch and transport of injured victims to the trauma center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This study demonstrated no significant difference in prehospital times, scene time, or transport duration for patients who sustained GSWs when acoustic detection occurred compared to patients who experienced GSW when no acoustic detection occurred. The previous reports did find a difference in prehospital time in those associated with acoustic detection showing improved transport times but are geographically distinct [12,13].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This study demonstrated no significant difference in prehospital times, scene time, or transport duration for patients who sustained GSWs when acoustic detection occurred compared to patients who experienced GSW when no acoustic detection occurred. The previous reports did find a difference in prehospital time in those associated with acoustic detection showing improved transport times but are geographically distinct [12,13].…”
Section: Discussionmentioning
confidence: 80%
“…ADS use by police has been previously reported [2,[10][11][12][13]. ADS impact in gunshot survival may be less significant in smaller cities or those with sufficient trauma care resources, particularly in relation to the gun violence "hot spots" as demonstrated here [10][11][12][13]. While the utility of ADS coverage for an entire municipality may act as a deterrent to gunplay, the impact on healthcare remains mixed [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of prehospital interventions by police 10,14 would logically result in shorter prehospital times. Several recent studies on the relationship between prehospital time and mortality have shown that not all patients benefit from shorter prehospital times.…”
Section: Discussionmentioning
confidence: 99%
“…This could include changes to policing that result in closer relationships with at-risk communities and trauma center educational outreach. Though somewhat controversial, the gunshot detection technology ShotSpotter has been used with considerable success in some cities 14,16 and has the potential to mitigate delays in the notification that a firearm assault has occurred. Finally, and perhaps most importantly, we believe our findings support the consideration of implementing police transport of gunshot victims in New Orleans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation